Randomized clinical trial comparing two vessel‐sealing devices with crush clamping during liver transection. Issue 13 (29th September 2016) - Ichida, A.; Hasegawa, K.; Takayama, T.; Kudo, H.; Sakamoto, Y.; Yamazaki, S.; Midorikawa, Y.; Higaki, T.; Matsuyama, Y.; Kokudo, N.
Abstract : Background: Previous RCTs have failed to demonstrate the usefulness of combining energy devices with the conventional clamp crushing method to reduce blood loss during liver transection. Here, the combination of an ultrasonically activated device (UAD) and a bipolar vessel‐sealing device (BVSD) with crush clamping was investigated. Methods: Patients scheduled to undergo hepatectomy at the University of Tokyo Hospital or Nihon University Itabashi Hospital were eligible for this parallel‐group, single‐blinded randomized study. Patients were assigned to a control group (no energy device used), an UAD group or a BVSD group. The primary endpoint was the volume of blood loss during liver transection. Outcomes of the control group and the combined energy device groups (UAD plus BVSD) were first compared. Pairwise comparisons among the three groups were made for outcomes for which the combined energy device group was superior to the control group. Results: A total of 380 patients were enrolled between July 2012 and May 2014; 116 patients in the control group, 122 in the UAD group and 123 in the BVSD group were included in the final analysis. Median blood loss during liver transection was lower in the combined energy device group (245 patients) than in the control group (116 patients): median 190 (range 0–3575) versus 230 (range 3–1570) ml ( P  = 0·048). Pairwise comparison revealed that blood loss was lower in the BVSD group than in the control group ( P  = 0·043). Conclusion: The use of energy devices combined with crush clamping reduced blood loss during liver transection. Registration number: C000008372 (www.umin.ac.jp/ctr/index.htm ). Abstract : Sealing devices may reduce blood loss